Enhanced thermal conductivities of epoxy nanocomposites via incorporating in-situ fabricated hetero-structured SiC-BNNS fillers - Han, Yixin; Shi, Xuetao; Yang, Xutong; Guo, Yongqiang; Zhang, Junliang; Kong, Jie; Gu, Junwei (Composites science and technology, 2020)
Novel hetero-structured silicon carbide-boron nitride nanosheets (SiC-BNNS) by sol-gel and in-situ growth method were performed as thermally conductive & insulating fillers, and the SiC-BNNS/epoxy thermally conductive nanocomposites were then prepared by blending-casting approach. Synthesized hetero-structured SiC-BNNS fillers have synergistic improvement effects on the thermal conductivities of the SiC-BNNS/epoxy nanocomposites. When the amount of hetero-structured SiC-BNNS fillers is 20 wt% (SiC-BNNS, 1/1, w/w), the thermal conductivity coefficient (λ) value of the SiC-BNNS/epoxy nanocomposites (0.89 W/mK) is 4.1 times that of pure epoxy resin (0.22 W/mK), and 2.1, 1.4, and 1.7 times of SiC/epoxy (0.43 W/mK), BNNS/epoxy (0.62 W/mK), and (SiC/BNNS)/epoxy thermally conductive nanocomposites (0.52 W/mK) with the same amount of fillers (20 wt% single BNNS, SiC, or SiC/BNNS hybrid fillers), respectively. Meantime, the obtained (SiC-BNNS)/epoxy thermally conductive nanocomposites also demonstrate favorable electrical insulating properties, and the breakdown strength, volume resistivity as well as surface resistivity is 22.1 kV/mm, 2.32 × 1015 Ω cm, and 1.26 × 1015 Ω cm, respectively.